Life-threatening Events in Respiratory Medicine: Misconnections of Invasive and Non-invasive Ventilators and Interfaces - Stieglitz, S.; George, S.; Priegnitz, C.; Hagmeyer, L.; Randerath, W. (Pneumologie, 2013)
Purpose: Both the parallel use of intensive care unit (ICU)-ventilators and ventilators dedicated to non-invasive ventilation (NIV), as well as the construction of some expiratory valves in single circuit breathing tubes may lead to misconnections which are potentially fatal for the patient. Methods: We demonstrate first a case of a misconnected expiratory valve in a patient with invasive home ventilation. In a second case, the mistaken connection of a non-invasive ventilator to an endotracheal tube leading to carbon dioxide (CO2)-rebreathing is demonstrated. A third case describes a patient with home non-invasive ventilation who had been delivered a non-vented mask out-of-hospital, likewise leading to CO2-rebreathing.Conclusion: Human error is the main reason for critical incidents in medicine and the most serious unintended events often involve mechanical ventilation. A regular instruction of medical staff and patients is necessary. The demonstrated misconnections are examples of latent errors “waiting to happen”. To prevent these errors from being made in the future, technological solutions similar to the aviation effort to improve safety are needed.